PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN KEPMENDESA PDTT NOMOR 136 PADA BUMDES MARITIM JAYA KABUPATEN TANAH BUMBU TAHUN 2024 - Endang Permata Sari; Noor Amelia; Rizky Mega Arini; Deafatunnizwa Ulfida; Muhammad Akbar (UNIVERSITAS DHARMAWANGSA, 2026)
Transparent and accountable financial management is an essential requirement for the sustainability of Village-Owned Enterprises (BUMDes) towards improving the rural economy institutions. Many BUMDes, however, remain challenged in organizing proper financial reporting in accordance with established standards, including BUMDes Maritim Jaya in Tanah Bumbu Regency. This study focuses on explaining the steps involved in preparing financial reports at BUMDes Maritim Jaya based on the Ministry of Village, Development of Disadvantaged Regions, and Transmigration Regulation Number 136 of 2022 concerning Guidelines for Preparing BUMDes Financial Reports. A qualitative descriptive method with quantitative data was employed, using observation and documentation techniques for data collection. The results indicate that after assistance and the implementation of standardized financial report formats, all financial transactions were recorded systematically, fixed assets were inventoried and depreciated, and comprehensive financial reports—including income statements, changes in equity, financial position reports, and notes to the financial statements—were successfully prepared. The application of these standards contributed to enhancing transparency and accountability in BUMDes financial management. Nevertheless, BUMDes Maritim Jaya still experienced losses as revenues were insufficient to cover operational expenses and asset depreciation. This study is projected to provide a useful reference for applying accounting standards at the village level and to strengthen BUMDes financial governance.